Ratio of Circulating Estrogen Receptors Beta and Alpha (ER¿/ER¿) Indicates Endoscopic Activity in Patients with Crohn¿s Disease - Linares, P.M.; Algaba, A.; Urzainqui, A.; Guijarro Rojas, M.; González Tajuelo, R.; Garrido, J.; Chaparro, M.; Gisbert, J.P.; Bermejo, F.; Guerra, I.; Castellano, V.; Fernández Contreras, María Encarnación (My University, 2017)
Background: Data supporting a role of female hormones and/or their receptors in inflammatory bowel disease (IBD) are increasing, but most of them are derived from animal models. Estrogen receptors alpha (ER¿) and beta (ER¿) participate in immune and inflammatory response, among a variety of biological processes. Their effects are antagonistic, and the net action of estrogens may depend on their relative proportions. Aim: To determine the possible association between the balance of circulating ER¿ and ER¿ (ER¿/ER¿) and IBD risk and activity. Methods: Serum samples from 145 patients with IBD (79 Crohn¿s disease [CD] and 66 ulcerative colitis [UC]) and 39 controls were retrospectively studied. Circulating ER¿ and ER¿ were measured by ELISA. Disease activities were assessed by clinical and endoscopic indices specific for CD and UC. Results: Low values of ER¿/ER¿ ratio were directly associated with clinical (p = 0.019) and endoscopic (p = 0.002) disease activity. Further analyses by type of IBD confirmed a strong association between low ER¿/ER¿ ratio and CD clinical (p = 0.011) and endoscopic activity (p = 0.002). The receiver operating curve (ROC) analysis showed that an ER¿/ER¿ ratio under 0.85 was a good marker of CD endoscopic activity (area under the curve [AUC]: 0.84; p = 0.002; sensitivity: 70%; specificity: 91%). ER¿/ER¿ ratio was not useful to predict UC activity. Conclusions: An ER¿/ER¿ ratio under 0.85 indicated CD endoscopic activity. The determination of serum ER¿/ER¿ might be a useful noninvasive screening tool for CD endoscopic activity.